2003
DOI: 10.3354/meps263247
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, abundance and mortality of cod and haddock eggs and larvae on Georges Bank in 1995 and 1996

Abstract: The eggs and larvae of developing year-classes for cod Gadus morhua and haddock Melogrammus aeglefinus on Georges Bank were sampled during monthly surveys in the winter and spring of 1995 and 1996. The distribution and abundance of the age groups or cohorts within the egg and larval populations were estimated during each survey. The displacement of the cohorts between surveys was largely consistent with advection by the climatological circulation pattern. Egg mortality rates, calculated from the decrease in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…This was the conservative approach since any correction for mortality would have moved the distributions toward the left (earlier in the year), resulting in greater separation between HDFs of juveniles and eggs. For comparison with the HDF of eggs (Mountain et al 2003), juvenile hatch dates were summed over 10 d intervals. To estimate relative survival, the HDFs of eggs and juveniles were first converted to relative HDFs by dividing the number in each interval by the total number in the sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was the conservative approach since any correction for mortality would have moved the distributions toward the left (earlier in the year), resulting in greater separation between HDFs of juveniles and eggs. For comparison with the HDF of eggs (Mountain et al 2003), juvenile hatch dates were summed over 10 d intervals. To estimate relative survival, the HDFs of eggs and juveniles were first converted to relative HDFs by dividing the number in each interval by the total number in the sample.…”
Section: Methodsmentioning
confidence: 99%
“…While the relatively small sample size in some years limited the degree of resolution possible, the considerably larger sample of the 1998 year class revealed a broad and relatively smooth distribution of birth dates when binned into 10 d intervals. HDFs based on late egg stage abundance sampled as part of the GLOBEC broad-scale cruises between January and June of 1995 to 1999, indicated that haddock hatched between January and May, with a pronounced peak in the first half (Mountain et al 2003) and on YOY haddock with relative survival (relative HDF juveniles/ relative HDF eggs) for (a) 1995, 1996, 1997 and 1999 combined and for (b) 1998 of April in most years (Mountain et al 2003, D. Mountain pers. comm.).…”
Section: Temporal Patterns In Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, at about half of the stations, a 10 m 2 MOCNESS (3 mm mesh) sampled older fish larvae and other planktonic organisms. The full sampling plan and methodology can be found in Mountain et al (2003Mountain et al ( , 2008. The density and total abundance of hatching larvae were estimated from the distribution of late stage eggs corrected for estimated egg mortality.…”
Section: Methodsmentioning
confidence: 99%
“…Here we combined data on the seasonal and inter-annual variability in mortality rates of Atlantic cod and haddock obtained from 24 cruises (Mountain et al 2003(Mountain et al , 2008 with comparable data on the seasonal and ontogenetic trends in larval growth rates (Buckley & Durbin 2006. We examined models relating M to hatch date, photoperiod, and water temperature.…”
Section: Introductionmentioning
confidence: 99%